The best recipe: fat-based, protein-based, single amino acids?. Issue 4 (August 2020) - Singer, Pierre; Glass, Yehuda D.; Kagan, Ilya
Abstract : Purpose of review: Instead of comparing iso versus low energy or high versus low protein intake, the proportions between nutrients and the effects of specific amino or fatty acids may yield promising benefits for the nutritional therapy of critically ill patients. Recent findings: Larger proportion of carbohydrates than lipids is usual in most of the commercial products. However, patients suffering from sepsis and from acute kidney injury preferentially utilize lipids. Parenteral omega-3-fatty acids, in particular, may be beneficial. Protein source and amount are important factors to achieve the best absorption and an improved nitrogen balance. Hydrolyzed whey protein reaches the highest amino acid plasma level if administered in large doses (35% of the measured energy expenditure). Muscle mass preservation may be achievable with large protein intake. β-Hydroxy-β-methylbutyrate has been shown to improve muscle strength in a large meta-analysis. Summary: The nutritional therapy should take into account the fact that lipids are more oxidized. Intravenous lipid emulsions containing olive and fish oil are preferred, improving morbidity significantly in a recent meta-analysis. Enteral protein should be selected carefully according to protein source, origin and amount. Hydrolyzed whey protein improves nitrogen balance. The ultimate goal is to preserve muscle mass and muscle function. β-Hydroxy-β-methylbutyrate may improve muscle strength.